Pengaruh Kualitas Pelayanan Dan Fasilitas Terhadap Kepuasan Pelanggan Pada Divisi Servis Auto2000 Cirebon - Imas, Imas; Sutiyajaya, Lulu; Tirto Santoso, Pangestu (POLITEKNIK LP3I, 2025)
This study aims to determine the effect of service quality and facilities partially or simultaneously on customer satisfaction in the Auto2000 Cirebon Service Division, the population in this study is customers who have used services or replacement spare parts at the Auto2000 Cirebon Service workshop and samples taken by 93 respondents. The method in this study uses questionnaires.